Role of Paeonol in an Astrocyte Model of Parkinson’s Disease - Ye, Maosheng (Med Sci Monit, 2017)
BACKGROUND: Parkinson’s disease (PD) is characterized by a progressive degeneration of dopaminergic (DA) neurons in the substantia nigra pars compacta (SNc). Inflammation and neural degeneration are implicated in the pathogenesis of PD. Paeonol has been verified to attenuate inflammation. MATERIAL/METHODS: 1-methyl-4-phenylpyridnium ion (MPP+, 100 μM) was used to induce the cell model of PD in primary cultured astrocytes. Astrocyte cell viability and apoptosis were determined by 3-(4, 5-dimethyl-2-thiazolyl)-2, 5-diphenyl-2-H-tetrazolium bromide (MTT) assay and flow cytometry (FCM), respectively. Protein levels of cyclooxygenase-2 (COX-2) and inducible nitric oxide synthases (iNOS) in culture medium were tested by enzyme-linked immunosorbent (ELISA) assay. Protein levels of casapse-1, COX2, iNOS, B-cell lymphoma 2 (Bcl-2)-associated X protein (Bax), Bcl-2, and phosphorylated Jun N-terminal kinase (p-JNK)/phosphorylated extracellular signal-regulated kinase (p-ERK)/p-P38 were examined by Western blot. RESULTS: Pretreatment with paeonol remarkably rescued MPP+-induced cell viability reduction, up-regulation of cell apoptosis, caspase-1 activity, COX-2, iNOS, and Bax/Bcl-2 ratio in primary astrocytes. Furthermore, paeonol repressed MPP+ -induced elevation of p-JNK/p-ERK in primary cultured astrocytes. CONCLUSIONS: The present study found that paeonol protected cells from apoptosis by repressing the activation of the JNK/ERK related signalling pathway induced by MPP+ in astrocytes. We propose that paeonol is a neuroprotective agent for the treatment of PD patients, with great promise in the future.